O poder da palavra: a narrativa presente na aula de história na era das novas tecnologias - Almeida, João Marcello de Araújo Costa Lopes de (2017)
This paper proposes to analyze oral narrative of a History teacher in the classroom. Research has started with the study of History as a narrative; continued with the investigation of dialogue-based lecture as the path to build a historical narrative; and established a comparative study of classes in which the voices of teacher and students are the main element in contrast to a class in which the oral narrative of a video is the source of the content to be worked. From this, it is possible to understand that the teacher´s role, especially when talking about didactic transposition and historical explanation, is essential to the success of teaching and irreplaceable in relation to the use of any technological tool.